Occurrence of rhinoceros in the Free State, South Africa: a reassessment - Herman Jordaan; Pieter Fourie; Ryk Lues (Pachyderm)
The last rhinoceros in the Orange Free State is believed to have been shot at Renosterkop near Kroonstad in 1842. This is one of nine farms in the present-day Free State Province with rhenoster (rhinoceros in Afrikaans) as a prefix in their names. These place names, and the petroglyph of a rhinoceros made by indigenous people on boulders near Rhenosterkop, indicate the occurrence of rhinos in the area in late historical times. We examined historical photographs, maps and literature to gain a retrospective view of the ecology. We conclude that the habitat could have supported small numbers of white rhinos (Ceratotherium simum), but that there was probably insufficient browsing vegetation for the survival of black rhinoceros (Diceros bicornis) at these sites. Previous evidence of fossilized black rhino skulls from the province was discounted when these were found to be those of a hippopotamus and a predator. The reintroduction of rhinos to the Province began in 1962 when a white rhino was relocated from Natal Province to the Willem Pretorius Game Reserve. Since then, rhino numbers have increased significantly, and there are currently 669 white rhinos and 11 black rhinos on state and private land in Free State Province.